This** preview**
has intentionally

**sections.**

*blurred***to view the full version.**

*Sign up*
**Unformatted text preview: **4. lim ( x,y ) → (2 ,-3) ± 1 x + 1 y ² 2 = 1 36 12. lim ( x,y ) → ( π 2 , ) =-2 18. lim ( x,y ) → (2 , 2) x + y-4 √ x + y-2 = lim ( x,y ) → (2 , 2) ( √ x + y-2)( √ x + y +2) √ x + y-2 = lim ( x,y ) → (2 , 2) ( √ x + y + 2) = 4 24. lim P → (-1 4 , π 2 , 2 ) tan-1 ( xyz ) = tan-1 ³-π 4 ´ 30. (a) All ( x, y ) so that x 2-3 x + 2 6 = 0 ⇒ ( x-2)( x-1) 6 = 0 ⇒ x 6 = 2 and x 6 = 1 (b) All ( x, y ) so that y 6 = x 2 40. Along y = kx, k 6 = 0, lim ( x,y ) → (0 , 0) x + y x-y = lim x → x + kx x-kx = 1 + k 1-k ⇒ diferent limits For diferent values oF k , k 6 = 1 ⇒ Limit DNE...

View
Full Document

- Fall '06
- PANTANO
- Math, Calculus, Arc Length, Multivariable Calculus, Harshad number